(untitled) (Perner’s Contacts, 2007)
As experiences have shown, the point use of existing regional railway lines by local passenger rail transit vehicles is technically possible in principle. Although calling for a degree of outlay for specific adaptation measures that involve structures and/or vehicles, this outlay is small in comparison to the cost of building a genuine rail rapid transit system from scratch. From a technical perspective, however, operating one or other distinctive rail mode is always the ideal scenario. This alone enables the precise co-ordination of complete components with one another (in particular, platforms and vehicles). Compared to single-mode operation, to a certain degree hybrid operation represents a type of “emergency remedy”, within which compromises have to be struck between two “naturally” different rail systems.